What new in diagnostic and therapy type 1 diabetes? Part II - Otto-Buczkowska, Ewa (Przewodnik Lekarza/Guide for GPs, 2011)
Until recently the diagnostic criteria and division into the two main types of diabetes seemed clear enough. It was thought that just as islet autoantibodies and tendency to ketosis was a feature of type 1 diabetes, the insulin resistance and slow progress of the disease was typical of diabetes type 2. However, the latest study results and case reports supply evidence, which question that present order. The growing diagnostic abilities give new measures to broaden the studies of diabetes pathogenesis and pathophysiology. All those data contribute to a great need to verify the old diagnostic criteria for type diabetes. This article reviews also recent therapeutic future trends in the prevention and management of diabetes mellitus – transplantation, stopping immune destruction and promoting β-cell regeneration.